Fresno County Legal Services Holiday Party - Watkins, Howard K. (1976)
Front: Carmelita Peralta, Mary Ludy, William Leifer, Janice Pearson, Gloria Escalante, Alice Mendoza, Ruben Lucero; back: Doris Burnes, Betsy Temple, Elaine Harris, Charles Kahill, Janie Munoz, Howard Watkins, Verletz Hooks, Virginia Salmeron, Ray Starks